2017
DOI: 10.1289/ehp1330
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Perfluoroalkyl Substances and Cardiometabolic Risk in Children from the Spanish INMA Birth Cohort Study

Abstract: Background:Perfluoroalkyl substances (PFAS) may affect body mass index (BMI) and other components of cardiometabolic (CM) risk during childhood, but evidence is scarce and inconsistent.Objectives:We estimated associations between prenatal PFAS exposures and outcomes relevant to cardiometabolic risk, including a composite CM-risk score.Methods:We measured perfluorohexanesulfonic acid (PFHxS), perfluorooctanesulfonic acid (PFOS), perfluorooctanoic acid (PFOA), and perfluorononanoic acid (PFNA) in maternal plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(128 citation statements)
references
References 64 publications
5
119
4
Order By: Relevance
“…Trained staff measured WC using an inelastic tape (SECA model 201; SECA, Hamburg, Germany), measured in the midpoint between the right lower rib and the iliac crest, and after a slight breath out. Regression models were used to derive WC z‐scores standardized by age, sex, height, and cohort . At 4 years, WC measurement was not collected in the Gipuzkoa region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trained staff measured WC using an inelastic tape (SECA model 201; SECA, Hamburg, Germany), measured in the midpoint between the right lower rib and the iliac crest, and after a slight breath out. Regression models were used to derive WC z‐scores standardized by age, sex, height, and cohort . At 4 years, WC measurement was not collected in the Gipuzkoa region.…”
Section: Methodsmentioning
confidence: 99%
“…Regression models were used to derive WC zscores standardized by age, sex, height, and cohort. 29 At 4 years, WC measurement was not collected in the Gipuzkoa region. Abdominal obesity was defined as WC z-score > 1 SD.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…This has varied between studies with different levels of exposure and conflicts with other studies where null associations were reported. 39,40 Methodological considerations As previously noted, 5 it is important to rule out that the association between increasing PFAS levels and BW is mediated via shorter GA. Here we performed several different investigations of this issue and found no signs of such indirect effects.…”
Section: Different Associations In Girls and Boysmentioning
confidence: 99%
“…Among these substances, endocrine disruptor chemicals (EDCs), such as phthalates, bisphenol and hydroxypyrene, which can be found in oil and water resistant textile coatings, non-stick cookware, food container coatings, floor polish, fire-fighting foam, and industrial surfactants, are a class of suspected obesogenic contaminants persisting in the environment and humans [31]. EDCs have been also detected in cord blood samples, suggesting that exposure starts prenatally [32] and early life EDC exposures may perturb neuroendocrine systems involved in growth, energy metabolism, appetite, adipogenesis, and glucose-insulin homeostasis promoting childhood obesity development [33].…”
Section: Introductionmentioning
confidence: 99%